ANALISIS KESALAHAN SISWA SMK DALAM MENYELESAIKAN SOAL MATERI PERSAMAAN LINGKARAN BERDASARKAN TAKSONOMI SOLO PLUS DITINJAU DARI KEMAMPUAN MATEMATIKA DASAR - . Oktapiyanti; Risma Amelia (IKIP Siliwangi, 2020)
The purpose of this study is to describe the mistakes made by students in solving circle equation questions based on the SOLO plus taxonomy. The method that is used in this study is descriptive qualitative method with 9 subjects of XII grade vocational students in Cimahi. The data collection technique that was carried out is using a learning achievement test which consists of 4 question instruments describing the circle equation, interviewing techniques using the interview guide sheet instrument, and documentating. The results of this study are the overall percentage of students' answers in solving circle equation questions with high ability by 60%, students with medium ability by 50%, and students with low ability by 34%. The results of the analysis obtained based on the tests and the interviews are students find it difficult to solve circle equation questions. Then students' abilities are still at the Pre-structural, Unistructural, Multistructural, and Relational levels.